Validity and reliability of autofluorescence-based quantification method of dental plaque - Han, Sun-Young; Kim, Bo-Ra; Ko, Hae-Youn; Kwon, Ho-Keun; Kim, Baek-Il (Photodiagnosis and photodynamic therapy, 2015)
•We examined the potential of APQ method for new clinical plaque evaluation method.•APQ method showed excellent reliability and fair validity with conventional indices.•Possibilities to detect and quantify heavy plaque by QLF technology are highlighted. The aim of this study was to evaluate validity and reliability of autofluorescence-based plaque quantification (APQ) method. The facial surfaces of 600 sound anterior teeth of 50 subjects were examined. The subjects received dental plaque examination using Turesky modified Quigley Hein plaque index (QHI) and Silness & Löe plaque index (SLI). The autofluorescence images were taken before the plaque examination with Quantitative Light-induced Fluorescence-Digital, and plaque percent index (PPI) was calculated. Correlation between two existing plaque indices and the PPI of the APQ method was evaluated to find which level of plaque redness on tooth (ΔR) by the APQ method shows the highest correlation. The area under the ROC curve (AUC) analysis and intra- and inter-examiner reliability tests were performed. The PPIΔR20 of the APQ method showed a moderate correlation with two existing plaque indices (rho of QHI=0.48, SLI=0.51). This methodology fell in the fair category and it had an excellent reliability. The APQ method also showed possibility to detect heavy plaque with fair validity. The APQ method demonstrated excellent reliability, and fair validity, compared with 2 conventional indices. The plaque quantification described has the potential to be used in clinical evaluation of oral hygiene procedures.